Actors’ Interaction in Developing Village Tourism:A Case of Borobudur Tourism - Shanty Oktavilia; Indah Fajarini Sri Wahyuningrum; Sri Utami; Sri Hestiningsih Widiyanti; Wiwin Widiastuti; Herlina Kurniawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to develop a tourism village development strategy based on stakeholder interaction as an economic recovery effort. This descriptive qualitative research used the hexa-helix concept and was conducted in 20 tourist villages in the Borobudur Temple Area. This research uses primary and secondary data involving 42 respondents. It consists of Pokdarwis (Tourism Awareness Group) administrators, BUMDes (Village-Owned Enterprise) administrators, Balkondes managers, Cluster Discussion Forum (FRK) managers, as well as village officials who have information related to tourism village business profile. The results of this research are as follows: Firstly, the central government can synergize with regional governments and related technical agencies to carry out breakthrough tourism policy innovations in the Borobudur area, namely by simplifying permits to encourage investment while preserving the village environment. Second, the business world and industry can contribute through CSR programs by facilitating training and mentoring activities needed by the community. Third, universities have a moral responsibility in village development. One way that can be done is by committing to involve students directly in developing the Borobudur tourist area. Fourth, community organizations are government partners who catalyze changes. Fifth, mass media is a forum for promoting the potential of the Borobudur tourist area by utilizing the digital era to reach a wider community